The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/aic.12258
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive kinetic model for high‐temperature free radical production of styrene/methacrylate/acrylate resins

Abstract: in Wiley Online Library (wileyonlinelibrary.com).n-Butyl methacrylate/styrene/n-butyl acrylate (BMA/ST/BA) high-temperature starved-feed solution semibatch copolymerization and terpolymerization experiments with varying monomer feed composition, final polymer content, monomer feed time, and reaction temperature were carried out. A comprehensive mechanistic terpolymerization model implemented in PREDICI includes methacrylate depropagation, acrylate backbiting, chain scission, and macromonomer propagation, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(135 citation statements)
references
References 58 publications
10
125
0
Order By: Relevance
“…The profiles shown in Figure are typical of starved‐feed operation: monomer concentrations remain low and polymer average MWs quickly attain constant values due to the fixed ratio of initiator to monomer that is fed . The feeding strategy minimizes copolymer composition drift, with the instantaneous composition of the polymer formed controlled by the monomer ratios in the feed.…”
Section: Resultsmentioning
confidence: 98%
“…The profiles shown in Figure are typical of starved‐feed operation: monomer concentrations remain low and polymer average MWs quickly attain constant values due to the fixed ratio of initiator to monomer that is fed . The feeding strategy minimizes copolymer composition drift, with the instantaneous composition of the polymer formed controlled by the monomer ratios in the feed.…”
Section: Resultsmentioning
confidence: 98%
“…These values were used to provide a good description of the high temperature semibatch copolymerization system and also terpolymerization propagation kinetics with butyl methacrylate as a third monomer. [8][9][10] In another work, Garcia et al [ 1 ] investigated the ability of the terminal and implicit penultimate models to represent experimental conversions and compositions of the St/ n-BA system. The authors concluded that the terminal model was not able to predict well the copolymerization rate, which was then fi t using the penultimate model with s 1 = 0.009 and s 2 = 1.153 for radical reactivity ratios of n -BA and St, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For the reactions common with FRP, intrinsic rate coefficients reported in literature are used. [68][69][70][71] For activation of the ATRP initiator a value of 3.1 L Á mol À1 Á s À1 is considered based on the experimental study of Seeliger and Matyjaszewski. [72] The remaining secondary and tertiary activation and deactivation intrinsic rate coefficients are adjusted according to the experimental data of Ahmad et al [32] As discussed below, the obtained values are consistent with literature values and confirm the higher stability of tertiary macrospecies.…”
Section: Kinetic Modelmentioning
confidence: 99%